Assessment of Solar Energy Potential and Radiation Impact in the Federal Capital Territory and Nasarawa State, Nigeria. - Tor, Terkimbi; Nyam, George Gala; Samson, Damilola Oluwafemi; Asake, Jonathan; Iortim, Denis Mkur (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
This study assesses the solar energy potential and radiation impact in the Federal Capital Territory (FCT) and Nasarawa State (NS), Nigeria, over ten years. Two main analyses were carried out: electricity generation potential and descriptive statistical analysis. It was observed that the solar radiation for FCT ranges from 11.4 MJm⁻² day⁻¹ to 22.0 MJm⁻² day⁻¹, with an average value of 17.6 MJm⁻² day⁻¹, and a total annual solar radiation of 211.7 MJm⁻² day⁻¹. In contrast, NS ranges from 11.8 MJm⁻² day⁻¹ to 22.2 MJm⁻² day⁻¹, with an average value of 17.5 MJm⁻² day⁻¹, and a total annual solar radiation of 209.6 MJm⁻² day⁻¹. During the off-rainy season, both regions demonstrated high reliability for solar power generation, with FCT showing a reliability of 0.62 and NS a reliability of 0.56. The performance of photovoltaic systems was also evaluated using a 550 W PV panel with FCT having a value of 6.206 x 107 MWh annually, while NS can produce 2.27 x 108 MWh. The observed clearness index (K_t) ranges between 0.414 – 0.665 and 0.432 – 0.662 for both FCT and NS. Moreover, the skewness values for FCT and NS are -0.379 and -0.220, respectively, suggesting that the distribution’s tail is slightly shifted towards the left for both FCT and NS. The kurtosis results for both regions exhibit values of approximately FCT (1.322) and NS (1.168), indicating that the distributions are platykurtic. These results suggest that both regions have substantial potential for solar energy generation.